GNSS direction finding - Grimm, David (Geodesy and Cartography, 2012)
GNSS receivers provide position information in a convenient way. However, additional orientation information cannot be fulfilled directly by a single antenna receiver up to now. This paper describes an approach for determining the orientation by a single GNSS receiver based only on its own static observations. As estimable base quantity, satellite positions are used as a reference in the moment of measuring. For that purpose the direction of each satellite’s signal has to be known in relation to the antenna. In order to obtain this information, the signal strength of each satellite is measured. A systematical modulation of the signal, realized by rotating shading, is able to provide the required direction information approximately.GNPS krypties nustatymasSantrauka. Globalinės navigacinės palydovinės sistemos (GNPS) imtuvai teikia informaciją patogiu būdu, tačiau išsamios papildomos informacijos apie kryptis, taikant vieną imtuvą su antena, gauti neįmanoma. Aprašoma, kaip nustatyti kryptį taikant vieną GNPS imtuvą, remiantis tik statiniais matavimais. Įvertinant pagrindinį dydį matavimų metu palydovų padėtys yra laikomos atrama. Tam tikslui yra žinomos kryptys antenos atžvilgiu į kiekvieną palydovą. Matuojama kiekvieno palydovo signalo stipris. Sisteminė signalo moduliacija besisukančia uždanga įgalina apytiksliai nustatyti reikalingą kryptį.First published online: 03 Aug 2012